Evaluation of the new GenoType NTM-DR kit for the molecular detection of antimicrobial resistance in non-tuberculous mycobacteria. (28th February 2017) - Mougari, Faiza; Loiseau, Jade; Veziris, Nicolas; Bernard, Christine; Bercot, Béatrice; Sougakoff, Wladimir; Jarlier, Vincent; Raskine, Laurent; Cambau, Emmanuelle; ,
Abstract : Objectives: Non-tuberculous mycobacteria (NTM) are emerging pathogens causing difficult-to-treat infections. We tested a new assay (GenoType NTM-DR) that detects natural and acquired resistance mechanisms to macrolides and aminoglycosides in frequently isolated NTM species. Methods: Performance was assessed on 102 isolates including reference strains [16 Mycobacterium avium, 10 Mycobacterium intracellulare, 8 Mycobacterium chimaera, 15 Mycobacterium chelonae and 53 Mycobacterium abscessus (including subsp. abscessus isolates, 18 with a t28 in erm(41) and 10 with a c28, 13 subsp. bolletii isolates and 12 subsp. massiliense isolates)]. Genotypes were determined by PCR sequencing of erm(41) and rrl for clarithromycin resistance and of the 1400–1480 rrs region for aminoglycoside resistance. Phenotypes were determined by MIC microdilution. Results: GenoType NTM-DR yielded results concordant with Sanger sequencing for 100/102 (98%) isolates. The erm(41) genotypic pattern was accurately identified for M. abscessus isolates . Mutations in rrl were detected in 15 isolates (7 M. avium complex, 5 M. abscessus and 3 M. chelonae ) with acquired clarithromycin resistance harbouring rrl mutations (a2057c, a2058g, a2058t or a2059c). Mutations in rrs were detected in five isolates with amikacin resistance harbouring the rrs mutation a1408g. In two isolates, the NTM-DR test revealed an rrl mutation (initial sequencing being WT), which was confirmed by re-sequencing. The test results were concordant with phenotypic susceptibility testing in 96/102 (94.1%) isolates, with four clarithromycin-resistant and two amikacin-resistant isolates not harbouring mutations. Conclusions: The GenoType NTM-DR test is efficient in detecting mutations predictive of antimicrobial resistance in M. avium complex, M. abscessus and M. chelonae.